Designed protein G core variants fold to native-like structures: Sequence selection by ORBIT tolerates variation in backbone specification - Ross, Scott A. (Cold Spring Harbor Laboratory Press, 2001)
The solution structures of two computationally designed core variants of the β1 domain of streptococcal protein G (Gβ1) were solved by (1)H NMR methods to assess the robustness of amino acid sequence selection by the ORBIT protein design package under changes in protein backbone specification. One variant has mutations at three of 10 core positions and corresponds to minimal perturbations of the native Gβ1 backbone. The other, with mutations at six of 10 positions, was calculated for a backbone in which the separation between Gβ1's α-helix and β-sheet was increased by 15% relative to native Gβ1. Exchange broadening of some resonances and the complete absence of others in spectra of the sixfold mutant bespeak conformational heterogeneity in this protein. The NMR data were sufficiently abundant, however, to generate structures of similar, moderately high quality for both variants. Both proteins adopt backbone structures similar to their target folds. Moreover, the sequence selection algorithm successfully predicted all core χ(1) angles in both variants, five of six χ(2) angles in the threefold mutant and four of seven χ(2) angles in the sixfold mutant. We conclude that ORBIT calculates sequences that fold specifically to a geometry close to the template, even when the template is moderately perturbed relative to a naturally occurring structure. There are apparently limits to the size of acceptable perturbations: In this study, the larger perturbation led to undesired dynamic behavior.